Effects of implementing the ECRIF framework on oral production participation in communicative English courses - Chavarría Nájera, Nazareth 1998- (2022)
This thesis project analyzes the ECRIF Framework and its effects in oral production participation when utilized in Costa Rican English communicative lessons. Ten 12- to 14-year-old students participated in an ECRIF-based conversational online course to learn the target language. During the language learning process, researchers applied questionnaires, observations worksheets, and self-assessment checklists to identify and measure factors that affect oral production in ECRIF- based lessons such as participation, motivation, safety, and communicative skills. Data was collected, triangulated, and analyzed under a QUAL-quan mixed-method approach to measure the effectiveness of the framework to promote oral production. Results suggest that ECRIF- based lessons can increase students' oral production and participation. However, insufficient data and unpredictable factors when developing virtual lessons did not allowed to established definitive results. Adaptations and enhancements are necessary to ensure the effectiveness of the ECRIF-based lessons in an online setting.